2016
DOI: 10.4081/hr.2016.6110
|View full text |Cite
|
Sign up to set email alerts
|

Serum Endocan Levels in Children with Febrile Neutropenia

Abstract: Endocan is an endotelial cell specific molecule; previous studies have shown that serum endocan levels increased in cancer and sepsis and are also related to the severity of sepsis. There are no clinical study about serum endocan levels in children with febrile neutropenia. The aim of this study was to evaluate serum endocan levels in pediatric leukemia patients with febrile neutropenia (n=33) and compare them with children with leukemia without fever (n=33) and also with healthy children (n=24). The median se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
(23 reference statements)
1
3
0
Order By: Relevance
“…This result was also supported by the present study indicating that PCT, WBC, CRP levels and the presence of fever were not correlated. In the present study, a positive and significant correlation was found between the Endocan level and the fever elevated after 24 h and this is parallel to the studies conducted with septic patients [26] and febrile neutropenic patients [27]. This is associated with the fact that inflammation or infection can show itself with fever without impairment in laboratory data [27].…”
Section: Discussionsupporting
confidence: 88%
“…This result was also supported by the present study indicating that PCT, WBC, CRP levels and the presence of fever were not correlated. In the present study, a positive and significant correlation was found between the Endocan level and the fever elevated after 24 h and this is parallel to the studies conducted with septic patients [26] and febrile neutropenic patients [27]. This is associated with the fact that inflammation or infection can show itself with fever without impairment in laboratory data [27].…”
Section: Discussionsupporting
confidence: 88%
“…Signs of systemic activation of microvessels can be considered the accumulation of cast-off endothelial cells (CD144+ cells) in the bloodstream, as well as the soluble forms of certain adhesion receptors: endocan, E-selectin, VCAM-1 and ICAM-1 (Pierrakos and Vincent 2010;Dunne 2015;Kiral 2016). However, sE-selectin and sICAM-1, according to our data, can only be considered as additional criteria to estimate SIR (i.e., a relatively small amplitude of changes in blood concentration in sepsis and acute trauma) (Zotova et al 2016).…”
Section: Commonly Used Sir Indicatorsmentioning
confidence: 99%
“…Thus, the results from our previous study together with the results presented in Table S1 suggest that endocan is a better biomarker than the p14 endocan fragment for characterization of patient heterogeneity also for the majority of acute leukemia patients not requiring transfer to intensive care units for life-supportive therapy. Previous studies have shown that systemic endocan levels are low in patients with chemotherapy-induced neutropenia and no signs of complicating infections, the levels then increase during febrile neutropenia with increased CRP and then normalize when the signs of infection disappear during antibiotic treatment [3,78]. Thus, the systemic endocan level seems to increase as a part of the acute phase reaction during febrile neutropenia, both for children and adult patients.…”
mentioning
confidence: 92%